PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERMADI WIJAYA SIDOARJO - FAUZIYAH PUTRI LESTARI, IFFAH; SOESATYO, YOYOK (Jurnal Ilmu Manajemen (JIM), 2018)
The phenomenon of authoritarian leadership style in PT.Permadi Wijaya Sidoarjo which became an interesting problem and strongly influenced employee performance causing decreased work discipline. The type of research is quantitative approach with Stratified Random Sampling technique that is 86 respondents. Data collection techniques used questionnaires, observations, and documentation. The technique of data analysis using multiple linear regression with SPSS 20. The result of leadership style analysis is 2.061. While the work discipline of 4.245. Based on the probability that leadership style and work discipline have a positive significance on employee performance. Keywords: leadership style, work discipline, and employee performance.